Feed Efficiency, Tissue Growth and Energy Budget Changes during the Molting Cycle of Juvenile Mud Crab, Scylla serrata: Effects of Dietary Proteins, Fishmeal versus Soy Protein Concentrate - Ngoc Thi Bich Nguyen; Laurent Wantiez; Pierrette Lemaire; Liet Chim (Fishes, 2022)
Three isoenergetic diets differing in their fishmeal/soy protein concentrate (SPC) ratio were assessed on the tissue growth and energy budget of juvenile crabs Scylla serrata in postmolt stages (PMolt) and in intermolt stages (IMolt). The average growth rates on a dry matter basis were 2.064 ± 0.324% and 0.492 ± 0.08% initial BW.day−1 during PMolt and IMolt stages, respectively. The efficiencies of the feed conversion (FCE, %), protein retention (PRE, %) and energy retention (ERE, %) were similar for the three experimental diets. However, FCE, PRE and ERE in PMolt stages were four to five times higher than in IMolt stages. The feed intake, energy and protein required for growth in PMolt stages were obviously higher than in IMolt stages. The energy budgets (% total energy intake) were marginally affected by diet but were significantly affected by the molt stage. The maintenance energy was lower in PMolt stages (49.84 ± 4.9%) than in IMolt stages (83.33 ± 2.45%). The excess in maintenance energy in IMolt stages represents the portion set aside for the next molt: shell energy content (4.97 ± 0.31%) and energy for ecdysis (±28%). Conversely, recovery energy was significantly higher in PMolt stages (34.39 ± 0.99%) than in IMolt stages (8.33 ± 1.7%). In conclusion, SPC sustained good tissue growth and good feed utilization and can be used as a main source of dietary protein for crab juveniles in captivity.